The Long-Term Follow-Up of Patients with Cystine Stones: A Single-Center Experience for 13 Years - Takahashi, Toshifumi (J Clin Med, 2021)
Introduction: Cystine stone development is relatively uncommon among patients with urolithiasis, and most studies have reported only on small sample sizes and short follow-up periods. We evaluated clinical courses and treatment outcomes of patients with cystine stones with long-term follow-up at our center. Methods: We retrospectively analyzed 22 patients diagnosed with cystine stones between January 1989 and May 2019. Results: The median follow-up was 160 (range 6–340) months, and the median patient age at diagnosis was 46 (range 12–82) years. All patients underwent surgical interventions at the first visit (4 extracorporeal shockwave lithotripsy, 5 ureteroscopy, and 13 percutaneous nephrolithotripsy). The median number of stone events and surgical interventions per year was 0.45 (range 0–2.6) and 0.19 (range 0–1.3) after initial surgical intervention. The median time to stone events and surgical intervention was 2 years and 3.25 years, respectively. There was a significant difference in time to stone events and second surgical intervention when patients were divided at 50 years of age at diagnosis (p = 0.02, 0.04, respectively). Conclusions: Only age at a diagnosis under 50 was significantly associated with recurrent stone events and intervention. Adequate follow-up and treatment are needed to manage patients with cystine stones safely.